The complete genome of a viable archaeum isolated from 123‐million‐year‐old rock salt. (18th January 2016) - Jaakkola, Salla T.; Pfeiffer, Friedhelm; Ravantti, Janne J.; Guo, Qinggong; Liu, Ying; Chen, Xiangdong; Ma, Hongling; Yang, Chunhe; Oksanen, Hanna M.; Bamford, Dennis H.
Summary: Live microbes have been isolated from rock salt up to Permian age. Only obligatory cellular functions can be performed in halite‐buried cells. Consequently, their genomic sequences are likely to remain virtually unchanged. However, the available sequence information from these organisms is scarce and consists of mainly ribosomal 16S sequences. Here, live archaea were isolated from early Cretaceous (∼123 million years old) halite from the depth of 2000 m in Qianjiang Depression, Hubei Province, China. The sample was radiologically dated and subjected to rigorous surface sterilization before microbe isolation. The isolates represented a single novel species of H alobacterium, for which we suggest the name H alobacterium hubeiense, type strain H bt. hubeiense JI20‐1. The species was closely related to a Permian (225–280 million years old) isolate, H alobacterium noricense, originating from Alpine rock salt. This study is the first one to publish the complete genome of an organism originating from surface‐sterilized ancient halite. In the future, genomic data from halite‐buried microbes can become a key factor in understanding the mechanisms by which these organisms are able to survive in harsh conditions deep underground or possibly on other celestial bodies.